2006
DOI: 10.1097/01.ede.0000231279.30988.4d
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Exposure to Solvents and the Risk of Lymphomas

Abstract: This study suggests that aromatic and chlorinated hydrocarbons are a risk factor for non-Hodgkin lymphomas, and provides preliminary evidence for an association between solvents and Hodgkin disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(73 citation statements)
references
References 43 publications
4
67
0
2
Order By: Relevance
“…At first, exposure to benzene was associated only with an increased risk of acute myeloid leukaemia (Hayes et al 1997), but the induction of NHL by benzene has now also become apparent (O'Connor et al 1999, Mehlman 2006, Miligi et al 2006, Smith et al 2007, Zhang et al 2007, Steinmaus et al 2008. Benzene induces NHL in experimental studies of mice and rats (Farris et al 1993, Huff et al 1989.…”
Section: Introductionmentioning
confidence: 99%
“…At first, exposure to benzene was associated only with an increased risk of acute myeloid leukaemia (Hayes et al 1997), but the induction of NHL by benzene has now also become apparent (O'Connor et al 1999, Mehlman 2006, Miligi et al 2006, Smith et al 2007, Zhang et al 2007, Steinmaus et al 2008. Benzene induces NHL in experimental studies of mice and rats (Farris et al 1993, Huff et al 1989.…”
Section: Introductionmentioning
confidence: 99%
“…8). For proxy respondents, we have evaluated the distribution of some confounding factors between direct responders and proxies.…”
Section: Resultsmentioning
confidence: 99%
“…The size of the control group was somewhat greater than the largest diagnostic group (NHL and chronic lymphocytic leukemia cases combined). Details on case ascertainment and recruitment and control sampling procedures have been described previously (8).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The increased risk was found only for workers with an average exposure of 25 ppm benzene (RR = 4.7). Several other studies have reported an increased risk of non-Hodgkin lymphoma among workers occupationally exposed to benzene [157,[177][178][179] or to a mixture of organic solvents rather than benzene alone [177,180,181].…”
Section: Lymphomamentioning
confidence: 99%